Loss of Function of OsFBX267 and OsGA20ox2 in Rice Promotes Early Maturing and Semi-Dwarfism in γ-Irradiated IWP and Genome-Edited Pusa Basmati-1 - Andrew-Peter-Leon, M. T.; Selvaraj, Ramchander; Kumar, K. K.; Muthamilarasan, Mehanathan; Yasin, Jeshima Khan; Pillai, M. Arumugam (Frontiers in Plant Science, 2021)
Targeted mutagenesis is now becoming the most-favoured methodology to improve traits in popular rice cultivars selectively. Understanding the genetic basis of already available mutants could be the first step in designing such experiments. Improved White Ponni (IWP), a popularly grown South Indian rice variety, was subjected to γ irradiation to develop WP-22-2, an M6 line superior in semi-dwarfism, early flowering, high yield, and having grain qualities similar to IWP. Exogenous application of gibberellic acid (GA3) on WP-22-2 resulted in the elongation of shorter internodes to a level similar to IWP. Expression profiling of six genes regulating plant height showed their differential expression pattern at different time-points post-GA3 treatment. Further, sequencing of WP-22-2 and IWP genomes revealed several SNPs and large-scale deletions in WP-22-2. The conversion of functional codons to stop codon was observed in OsGA20ox2 and OsFBX267, which have reported roles in regulating semi-dwarfism and early flowering, respectively. Loss-of-function of OsGA20ox2 and OsFBX267 in WP-22-2 resulted in reduced plant height as well as early flowering, and the same has been confirmed by editing OsGA20ox2 in the rice variety, Pusa Basmati1 (PB1), using the CRISPR-Cas9 approach. Targeted editing of OsGA20ox2 in PB1 conferred shorter plant height to the edited lines compared to wild-type. Altogether, the study provides evidence on mutating OsGA20ox2 and OsFBX267 genes to develop early maturing and semi-dwarf varieties that can be released to the farmers after functional characterization and field trials.